Struktur Dan Komposisi Vegetasi Mangrove Di Kawasan Rehabhatasi Mangrove Pantai Pemalang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT Mangrove rehabilitation efforts along Pemalang Coast to improve ecosystem function have been carried out since 1990. Rhizophora mucronata seedlings were planted every year at spacing of 3 x 0.5 m. The objective of this study was to know its sucrIssion in term of composition and structure of the existing planting. The research design used was Factorial Experiment in Randomized Complete Block Design with locations as blocks and planting years as treatments. The number of locations was 3 whereas the number of planting years was 4, so there were 12 experimental units. Each of them consisted of 5 plots of 5x5 m2. The parameters measured in each experimental units were density, height, diameter, canopy width,and habitat chemico-physical characteristics. The results showed that composition of mangrove after two and five year age of rehabilitation consisted of two species, namely, Rmucronata (bakau) as a planted species andAvicennia marina (api-api) as an invation species.A marina grew faster than Rmucronata in three to five years after planting and formed two canopy layers : top layers and second layers. Interaction with environmental factors showed that vegetation density was positively correlated with total N, available P, K and organic matter content. The joint experimental units resulted the improvethent of habitat from sea to land in the mangrove aged 2 to 5.